2003
DOI: 10.1017/s0959269503001157
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future in Acadian French

Abstract: ab st rac t Our article presents a variationist analysis of future verb forms in Acadian French. The main variants considered are the inflected future (e.g. je partirai) and the periphrastic future (e.g. je vais partir). The purpose of this study is twofold: a) it will determine the distribution of these variants and their linguistic correlates; b) it will compare the use of future verb forms with other varieties of French. Our results reveal that the inflected future is used with greater frequency in Acadian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
97
2
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(121 citation statements)
references
References 4 publications
14
97
2
8
Order By: Relevance
“…For instance, Poplack and Turpin (1999), who analyzed a corpus of vernacular Ottawa French, found that the PF accounted for 73%, the IF for 20%, and the present for only 7% of their 3594 occurrences. A similar dominance of the PF has been reported in most Canadian studies, with the exception of King and Nadasdi (2003), whose examination of Acadian French found slightly more IF than PF (present was excluded from their analysis). Most studies have thus concentrated on the IF and PF in an attempt to identify which factors encourage the use of one over the other.…”
Section: Canadian Varieties Of Frenchsupporting
confidence: 82%
See 2 more Smart Citations
“…For instance, Poplack and Turpin (1999), who analyzed a corpus of vernacular Ottawa French, found that the PF accounted for 73%, the IF for 20%, and the present for only 7% of their 3594 occurrences. A similar dominance of the PF has been reported in most Canadian studies, with the exception of King and Nadasdi (2003), whose examination of Acadian French found slightly more IF than PF (present was excluded from their analysis). Most studies have thus concentrated on the IF and PF in an attempt to identify which factors encourage the use of one over the other.…”
Section: Canadian Varieties Of Frenchsupporting
confidence: 82%
“…It is, however, interesting to note that accounts of future-time expression in Acadian French (e.g. Comeau 2011;King & Nadasdi 2003) did not find sentential negation to be a significant factor. The results for certainty, temporal distance, and LTI are not as consistent as those reported for sentential polarity.…”
Section: Factormentioning
confidence: 95%
See 1 more Smart Citation
“…(Louise, 1995) La variation dans l'usage des temps verbaux du futur en français a déjà fait l'objet d'attention pour plusieurs variétés du français, qu'il soit hexagonal (JeanJean, 1988 ;Frankel, 1984) ou nord-américain (Deshaies et Laforge, 1981 ;Emirkanian et Sankoff, 1985 ;Poplack et Turpin, 1999 ;Chevalier, 1994 ;Zimmer, 1994 ;King et Nadasdi, 2003). Dans la majorité des études empiriques portant sur la variation, l'intérêt des chercheurs a porté sur l'alternance entre les deux variantes principales -le futur synthétique et le futur analytique -auxquelles on a tenté d'associer des facteurs linguistiques ou sociaux explicatifs de l'usage.…”
Section: Introductionunclassified
“…His findings point to a reversal in the relative frequency of each form compared to those presented in earlier metropolitan studies, with a rate of 58.8% for the periphrastic future and 41.2% for the inflected future. Similarly, in the case of Acadian French, King and Nadasdi (2003) find that use of the inflected future generally dominates over the periphrastic form at 53% and 47% respectively, although Chevalier (1996) In view of such differential findings concerning the process of language change which seems to be impinging on use of the inflected form to differing extents in continental and Franco-Canadian contexts, as well as the discrepancy between prescriptive norms and real language usage in a FrancoCanadian context at least, the question arises as to how the L2 learner in general, and the instructed L2 learner in particular, will express futurity in his/her language usage, and in so doing, come to reflect either prescriptive grammatical norms or native speaker sociolinguistic norms.…”
Section: Arborescences Revue D'études Françaises Issn: 1925-5357 99mentioning
confidence: 94%